Association between helicobacter pylori chronic gastritis and atherosclerosis of carotid and coronary arteries in autopsy sample of Iraqi population - Ibraheem, Wafaa K.; Hamoudi, Salim R.; Al-Ani, Imad Matloub Dally; Mustafa Mahmoud, Mohammed Imad Al-Deen (Microscopy Society (Singapore), 2017)
Introduction: Chronic infection with Helicobacter pylori (H. pylori) had been implicated in the pathogenesis of atherosclerosis. The Aim of the study was to assess the relationship between H. pylori chronic gastritis, and the severity of atherosclerosis of the carotid and coronary arteries in a sample of Iraqi population. Methods: Autopsy tissue samples were taken from eighty four sequentially selected cadavers collected at the Institute of Forensic Medicine, Baghdad, Iraq. Samples were taken from the gastric antrum to study histopathological changes and detect the presence of H. pylori, and the common carotid and the coronary arteries to observe for the presence of atherosclerosis. The tissues were  xed in 10% formal saline and processed for light microscopy; the wall thickness of the atherosclerotic vessels (intima and media) was measured using speci c morphometric scale. Monoclonal mouse antihuman antibody CD34 was used for the detection of the adhesion molecule on the endothelial cells of the atheromatous vessels. Results: There was a signi cant relationship between H. pylori induced chronic gastritis and carotid artery atherosclerosis (p<0.05), but a statistically non-signi cant relationship (p>0.05) between coronary artery atherosclerosis and H. pylori chronic gastritis. CD34 adhesion molecule CD34 was significantly expressed on endothelial cells in atherosclerotic lesions of both carotid and coronary arteries as compared to non-atherosclerotic vessels (p<0.05). Conclusion: There was a significant crude association between presence of H. pylori with chronic gastritis and carotid artery atherosclerosis. On the other hand the association with coronary artery atherosclerosis was not significant.